Evaluating the Determinants of Retirement Annuity Fund Investment Intention in South Africa’s Retirement Savings Landscape - Zwane, Bonginkosi Keith; Marais, Alastair; Nyide, Celani John (International Journal of Economics and Financial Issues, 2025)
The growing concern over insufficient retirement savings in South Africa highlights the importance of understanding the factors that influence individuals’ decisions to invest in Retirement Annuity Funds (RAFs). The purpose of this study is to assess critical factors influencing an individual’s intention to invest in RAF in an emerging economy. The study examines the relationships between awareness and knowledge of RAFs, including their tax benefits, and financial literacy, and how these factors influence individuals’ intention to invest in RAFs. A quantitative research approach was employed, using structured surveys distributed to university employees in KwaZulu-Natal, South Africa. The findings reveal that while individuals have moderate to high awareness of RAF tax benefits, this knowledge does not significantly influence investment intention. Additionally, financial literacy was found to have a negative relationship with the intention to invest, suggesting that financially literate individuals may prefer alternative investment options. The study contributes to knowledge by highlighting these relationships, providing insights that can help the national treasury and financial service providers develop guidelines to improve awareness and knowledge to influence attitudes about the benefits of investing in a RAF.